2014
DOI: 10.1073/pnas.1412306111
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsive effects of brain oxidative metabolism on aggression

Abstract: Despite ongoing high energetic demands, brains do not always use glucose and oxygen in a ratio that produces maximal ATP through oxidative phosphorylation. In some cases glucose consumption exceeds oxygen use despite adequate oxygen availability, a phenomenon known as aerobic glycolysis. Although metabolic plasticity seems essential for normal cognition, studying its functional significance has been challenging because few experimental systems link brain metabolic patterns to distinct behavioral states. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 72 publications
13
99
1
1
Order By: Relevance
“…A recent study demonstrated a negative causal relationship between brain oxidative phosphorylation activity and territorial aggression in honey bees and fruit flies (24). Consistent with that study, we here specifically identified modulation of NADH dehydrogenase, the oxidative phosphorylation enzyme complex with the best-known relationship to territorial aggression (7,24). Oxidative phosphorylation genes were generally down-regulated in response to territory intrusion in mouse and honey bee, as in previous studies (7,24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent study demonstrated a negative causal relationship between brain oxidative phosphorylation activity and territorial aggression in honey bees and fruit flies (24). Consistent with that study, we here specifically identified modulation of NADH dehydrogenase, the oxidative phosphorylation enzyme complex with the best-known relationship to territorial aggression (7,24). Oxidative phosphorylation genes were generally down-regulated in response to territory intrusion in mouse and honey bee, as in previous studies (7,24).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with that study, we here specifically identified modulation of NADH dehydrogenase, the oxidative phosphorylation enzyme complex with the best-known relationship to territorial aggression (7,24). Oxidative phosphorylation genes were generally down-regulated in response to territory intrusion in mouse and honey bee, as in previous studies (7,24). The stickleback diencephalon showed the opposite pattern, possibly indicative of brain regional heterogeneity or species-level variation in the timing of the metabolic response.…”
Section: Discussionsupporting
confidence: 88%
“…These results were confirmed recently by studies revealing that mitochondrial oxidative phosphorylation is inhibited in the brain of aggressive bees in favour of aerobic glycolysis (Barros et al, 2015;Chandrasekaran et al, 2015;Li-Byarlay et al, 2014;Rittschof et al, 2015b). This holds true when comparing genetically aggressive bees with gentle ones, but also when comparing bees from the same background before and after exposure to IAA (Chandrasekaran et al, 2015).…”
Section: Brain Metabolismsupporting
confidence: 65%
“…This holds true when comparing genetically aggressive bees with gentle ones, but also when comparing bees from the same background before and after exposure to IAA (Chandrasekaran et al, 2015). Direct manipulation of the brain metabolism of bees confirmed this relation to be causal, because inhibiting oxidative phosphorylation increased the aggressiveness of treated bees (Li-Byarlay et al, 2014). How this shift in energy metabolism is acting is unknown.…”
Section: Brain Metabolismmentioning
confidence: 91%
“…This appears counterintuitive, although neurons may be optimized to reduce ATP consumption [74] and thus COX activity, which is linked to neural activation [35] and not necessarily directly correlated with neuron size. Behavioural phenotype also may be related to brain metabolic activity [75]. The variation in total brain metabolic activity in our study species indicates that F. subsericea worker task performance within and outside the nest may contribute to increased brain operation costs.…”
Section: (B) Colony-level Social Organization and Brain Evolutionmentioning
confidence: 73%